Willingness To Pay (WTP) Wisatawan dalam Pelestarian Lingkungan Paska Perubahan Cagar Alam Kamojang ke Taman Wisata Alam Kamojang - Purna Hindayani; Alnidi Safarach Bratanegara; Armandha Redo Pratama (School of Postgraduate Studies, Diponegoro Univer, 2024)
The research was conducted in the area of the change of the Kamojang Nature Reserve (CA) to the Kamojang Nature Tourism Park (TWA) so that there was an increase in the area of the Kamojang Natural Tourism Park which was previously 535.01 Ha to 2,391 Ha. The goal of this study was to identify willingness to pay for environmental conservation in TWA after changes in land area. The method used willingness to pay (WTP) for environmental conservation in tourist areas in TWA Kamojang and the factors that influence the WTP value by using logit regression. The results showed that the average willingness to pay by visitors (WTP) is Rp. IDR 51,887 per visit with the option of improving facilities and infrastructure, adding tourist activities such as adequate camping grounds and hot springs and educational tourism of natural and environmental knowledge at TWA Kamojang. The total WTP is estimated to reach IDR 680,339,623 per year. All of the independent variables such as gender, age, income, education, travel costs during the tour affected the willingness to pay (WTP). The most significant factors influencing the willingness to pay for environmental conservation in the TWA Kamojang was age. The management of TWA Kamojang is expected to develop nature tourism that takes into account the principles of environmental conservation